THE EFFECT OF FEMALE COMMISSIONERS, FEMALE DIRECTORS, FEMALE AUDIT COMMITTEES, AND LIQUIDITY ON THE FINANCIAL PERFORMANCE OF CONVENTIONAL COMMERCIAL BANKS LISTED ON THE INDONESIA STOCK EXCHANGE - Luthfiasari, Putri Aulia; Putra, Vicky Dzaky Cahaya (Jurnal Akuntansi dan Keuangan (JAK), 2025)
This research aims to analyze the influence of female boards of commissioners, female boards of directors, female audit committees, and liquidity on the financial performance of conventional commercial banks listed on the Indonesia Stock Exchange (IDX). The banking industry plays a crucial role in maintaining national financial stability, strict regulatory standards, and active involvement in the implementation of good corporate governance standards. Purposive sampling was used to obtain 23 banking samples for the period 2019–2024. The analysis process was applied using the STATA 17 method through panel data linear regression. The results show that female commissioners and female directors have a positive but insignificant effect on financial performance, while liquidity shows a significant positive effect. The findings imply that gender diversity and financial management contribute to improving bank performance.